2022
DOI: 10.1371/journal.pntd.0010047
|View full text |Cite
|
Sign up to set email alerts
|

The elimination of human African trypanosomiasis: Achievements in relation to WHO road map targets for 2020

Abstract: Background In the 20th century, epidemics of human African trypanosomiasis (HAT) ravaged communities in a number of African countries. The latest surge in disease transmission was recorded in the late 1990s, with more than 35,000 cases reported annually in 1997 and 1998. In 2013, after more than a decade of sustained control efforts and steady progress, the World Health Assembly resolved to target the elimination of HAT as a public health problem by 2020. We report here on recent progress towards this goal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
131
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(131 citation statements)
references
References 48 publications
(80 reference statements)
0
131
0
Order By: Relevance
“…Sleeping sickness (human African trypanosomiasis, HAT) is caused by sub-species of Trypanosoma brucei spread by tsetse flies ( Glossina ). In the 20 th Century there were three major epidemics of HAT, the most recent being in the late 1990s when up to >35000 cases were reported annually [ 1 ]. WHO declared the aim of eliminating HAT as a public health problem by 2020 and the complete interruption of transmission by 2030.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleeping sickness (human African trypanosomiasis, HAT) is caused by sub-species of Trypanosoma brucei spread by tsetse flies ( Glossina ). In the 20 th Century there were three major epidemics of HAT, the most recent being in the late 1990s when up to >35000 cases were reported annually [ 1 ]. WHO declared the aim of eliminating HAT as a public health problem by 2020 and the complete interruption of transmission by 2030.…”
Section: Introductionmentioning
confidence: 99%
“…Sub-species of Glossina fuscipes are the major vectors across a large swathe of Central Africa, extending across South Sudan, Uganda, the Democratic Republic of Congo (DRC), Central African Republic (CAR) and Chad [ 2 ]. Together, these countries contributed >90% (27296/32275) of all cases of gHAT reported globally in the period 2011–2020 [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In these contexts, alternative or additional strategies developed in Southern Mexico and Central America, based on an eco-bio-social approach and participatory research, have shown promising outcomes 12. The successful results obtained against lymphatic filariases13 14 and human African trypanosomiasis15 16 were also due, at least in part, to the use of multiple strategies, based on the integration of research outputs for improving medical surveillance and vector control (with insecticide-treated bed nets and insecticide impregnated screens, respectively) with an important component of participatory research.…”
Section: Impact Of Multidisciplinary Translational Researchmentioning
confidence: 99%
“…The diseases impose a severe burden on human and livestock health in sub-Saharan Africa [ 1 ]. Thirty-seven countries are affected, with more than 50 million cattle, 70 million small ruminants [ 2 ], and 55 million people at risk of contracting the diseases [ 3 ]. The Food and Agricultural Organization (FAO) of the United Nations estimates that Africa loses up to US$1.5 billion annually as a result of the disease [ 4 ].…”
Section: Introductionmentioning
confidence: 99%